Assessing the eco-compatibility of new generation sunscreen products through a combined microscopic-molecular approach. (1st December 2022) - Varrella, Stefano; Danovaro, Roberto; Corinaldesi, Cinzia
Abstract: There is now unequivocal evidence that sunscreen can severely affect marine ecosystems. However, so far, most studies have focused on the impact of single sunscreen ingredients rather than on the whole sunscreen products, which are released into the marine environment. In the present work, we investigated the ecological impact of six formulations, which represent the "new generation" organic UV filters such as diethylamino hydroxybenzoyl hexyl benzoate (DHHB), methylene bis-benzotriazolyl tetramethylbutylphenol (MBBT), ethylhexyl triazone (EHT), and bis-ethylhexyloxyphenol methoxyphenyl triazine (BEMT), which are progressively replacing the "old generation" organic UV filters (e.g., oxybenzone, octinoxate) banned in several countries of the world. The six formulations tested were characterized by a different combination of ingredients, on a model species particularly sensitive to environmental alterations: the sea urchin, Paracentrotus lividus . We investigated the sea urchin responses both in terms of gene expression and anomalies in embryonic development. We found that all sunscreen products containing only MBBT, DHHB, BEMT, and EHT as UV filters, are more eco-compatible than those also containing also ES, or other ingredients such as emollients and texturizing compounds, which may act synergistically causing molecular stress, morphological anomalies, and ultimately possible death. Overall, the results presented here provide new insights on the effects of sunscreen products based on "new generation" UV filters, and highlights the urgency of testing complete formulations, rather than just specific UV filters to ascertain the eco-compatibility of sunscreen products, to effectively minimize their impact on marine ecosystems. Graphical abstract: Image 1 Highlights: Sunscreen products based on new organic UV filters can have different ecological impacts. The impact of sunscreen products on marine life is not only due to UV filters. Molecular stress analyses are a very sensitive tool to assess sunscreens' impact. Sunscreens eco-compatibility should be tested on the whole product.